Hubungan Antara Kadar Feritin Dengan Kreatinin Serum Pada Anak Thalasemia Mayor - Muhammad Asih Pambudi (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background : Patients with thalassemia that underwent routine blood transfusion are developing iron overload. In the state of excess iron, ferritin levelS increase. When iron storage capacity has been depleted, free iron will cause tissue damage. One of that damaged organ is the kidney. One parameter used to know the function of kidney is GFR (Glomerular Filtration Rate). A sample way to estimate GFR is serum creatinine. Increased 1-2 mg/dL of creatinine serum showed a decrease in ±50% of GFR. Objective: To determine the correlation between ferritin levels and serum creatinine in Thalassemia Major children at Abdul Moeloek hospital in Lampung Province in 2019. Research Method: This research is analytic descriptive with a cross-sectional approach. The sampling technique used was purposive sampling using secondary data from the results of medical records diagnosed with thalassemia major at Abdul Moeloe Hospital, and analyzed on a univariate basis to determine the frequency and bivariate distribution using the chi-square test. Results: The statistical test results obtained p-value of 0.028, it can be concluded that there is a correlation between ferritin levels with serum creatinine in children with Thalassemia major . The results of the analysis also obtained an OR value of 3.88 (95% CI 1.29-11.59 ) which means that respondents who had ferritin levels were at risk (≥ = 1000) 3.88 times greater had high creatinine levels compared to those who had levels ferritin is not at risk (≤1000). Conclusion: There is a correlation between ferritin levels with serum creatinine in Thalassemia B Major children at Abdul Moeloek Hospital in Lampung Province in 2019.